Social, medical and self-perceived factors influencing postpartum screening of diabetes after gestational diabetes. (January 2014) - Minsart, A. F.; Vander Maelen, A.; Fontaine, V.; Kirkpatrick, C.
<x xml:space="preserve">Abstract</x> To assess factors related with postpartum testing for diabetes and the mothers' knowledge about their infant's future risk for diabetes and obesity, we asked 87 women with gestational diabetes who delivered during a 28-month period, to perform a postpartum glucose screening. They were then asked to answer a telephone questionnaire regarding risk perception of diabetes and infant's risk, and were invited to undergo further glucose testing if they missed the first test. Postpartum screening was assessed according to medical, sociodemographic and interview characteristics. A total of 42.5% of women escaped initial postpartum screening and 43.0% escaped secondary testing. Performance of postpartum testing was related with sub-Saharan origin, BMI < 25 kg/m2 and with high risk perception of developing permanent diabetes. Few women were informed about their infant's future risk.